2019
DOI: 10.3390/su11123269
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Sustainability of Residential Areas Using Rain Gardens to Improve Pollutant Capture, Biodiversity and Ecosystem Resilience

Abstract: Rain gardens have become a widespread stormwater practice in the United States, and their use is poised to continue expanding as they are an aesthetically pleasing way to improve the quality of stormwater runoff. The terms rain garden and bioretention, are now often used interchangeably to denote a landscape area that treats stormwater runoff. Rain gardens are an effective, attractive, and sustainable stormwater management solution for residential areas and urban green spaces. They can restore the hydrologic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 72 publications
0
17
0
2
Order By: Relevance
“…River oats also produce high seed abundance per plant (Neill 2020). Practitioners chose river oats for restoration plantings due to their shade and flooding tolerance, perennial reproductive strategy, and nursery propagation potential (Morash et al 2019; Neill 2020).…”
Section: Methodsmentioning
confidence: 99%
“…River oats also produce high seed abundance per plant (Neill 2020). Practitioners chose river oats for restoration plantings due to their shade and flooding tolerance, perennial reproductive strategy, and nursery propagation potential (Morash et al 2019; Neill 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Rain gardens are included in localized stormwater control measures (SCMs) [8]. One of the simpler definitions of a rain garden specifies it as a depressed area in a landscape with planted grass and flowering perennials that collect rainwater from roofs, driveways, or streets, allowing it to soak into the ground [9].…”
Section: Definitions and Nomenclaturementioning
confidence: 99%
“…There are also definitions that primarily consider the purposes and benefits of using rain gardens, rather than their construction. Rain gardens are effective low impact development (LID) practices that are used in residential areas to capture stormwater runoff, to recharge groundwater by infiltration, and to remove pollutants from the water before it enters local streams [8]. Phosphorus is an example of a pollutant that is removed [8].…”
Section: Definitions and Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…Frosi et al [15] and Morash et al [65] found evidence for large volumes of runoff along streets in urban areas to have higher concentrations of contaminants, which affects the soil and the biogeochemical processes within the soil body. This can negatively affect tree growth due to the accumulation of contaminants, such as de-icing salt, in the soil layer [66].…”
Section: Regulation Of Water Qualitymentioning
confidence: 99%